Power Consumption, Mixing Time, and Oxygen Mass Transfer in a Gas-Liquid Contactor Stirred with a Dual Impeller for Different Spacing - Hayder Mohammed Issa (Journal of Engineering)
Multiple or dual impellers are widely implemented in stirred contactors used in various biological processes like fermentation, water treatment, and pharmaceutical production. The spacing between impellers is considered as a crucial factor in designing of these types of contactors resulting in variation of oxygen mass transfer, mixing time, or power consumption for such biological system. A study of three parts was conducted to characterize the effect of the spacing between impellers on the most important parameters that related to biological contactor performance: oxygen mass transfer coefficient kla from the gas phase (air) to the liquid phase (water), mixing time, and power consumption for different operating rotational speeds (1.67–3.33 rps) and for three different spacing positions. The used impellers system in the study is a dual impeller system which consists of an inverted and bladed rotated cone (IBRC) and a pitched-blade up-flow propeller (PBPU). The experimental results showed that the shorter spacing (the lower PBPU in a higher position) is more convenient, as the achieved oxygen mass transfer coefficient has showed an improvement in its values with lower mixing time and with a slight alteration in power consumption.